(Eco)toxicological maps: A new risk assessment method integrating traditional and in silico tools and its application in the Ledra River (Italy). (October 2018) - Raitano, Giuseppa; Goi, Daniele; Pieri, Valentina; Passoni, Alice; Mattiussi, Michele; Lutman, Anna; Romeo, Isabella; Manganaro, Alberto; Marzo, Marco; Porta, Nicola; Baderna, Diego; Colombo, Andrea; et al.
Abstract: Contaminants giving rise to emerging concern like pharmaceuticals, personal care products, pesticides and Endocrine Disrupting Chemicals (EDCs) have been detected in wastewaters, as reported in the literature, but little is known about their (eco)toxicological effects and consequent human health impact. The present study aimed at overcoming this lack of information through the use of in silico methods integrated with traditional toxicological risk analysis. This is part of a pilot project involving the management of wastewater treatment plants in the Ledra River basin (Italy). We obtained data to work up a global risk assessment method combining the evaluations of health risks to humans and ecological receptors from chemical contaminants found in this specific area. The (eco)toxicological risk is expressed by a single numerical value, permitting the comparison of different sampling sites and the evaluation of future environmental and technical interventions. Highlights: Aim of this work was to assess risk due to emerging contaminants in WWTPs. We integrated in silico models with traditional chemicals analysis. A new (eco)toxicological index was developed The new index was applied to Ledra river as a real case study